Problematika Pembentukan Komponen Cadangan: Dilema Partisipasi Bela Negara di Tengah Ancaman Pemutusan Hubungan Kerja - Aditama Candra Kusuma; Aji Lukman Ibrahim (Direktorat Riset dan Pengabdian Kepada Masyarakat, 2022)
The issue that arises during the formation of the Reserve Component is theemployer's termination of workers who follow the Reserve Component. Thisstudy aims to determine the sanctions for employers who terminate theemployment of workers who participate in the selection of ReserveComponents, as well as the ideal future arrangement for employers whoterminate the employment of workers who participate in future selections. Inthis study, qualitative descriptive and data analysis techniques are presentedin accordance with normative legal research methods. So that the resultsobtained are that the appropriate sanctions for employers who terminateemployment, namely criminal sanctions, refer to the criminal provisions inLaw No. 23 of 2019 on the Management of National Resources for NationalDefense, as well as ideal future arrangements for employers who terminateemployment relationships, namely by imposing criminal provisions which mustfirst be reformulated in Article 78 paragraph (1) of Law No. 23 of 209 on theManagement of National Resources for National Defense.